Antimicrobial resistance and carbapenemase dissemination in Pseudomonas aeruginosa isolates from Libyan hospitals: a call for surveillance and intervention - Nasrin K. Gadaime; Randa N. Haddadin; Asem A. Shehabi; Intisar N. Omran (Libyan Journal of Medicine)
Pseudomonas aeruginosa is a multidrug-resistant bacterium capable of forming biofilms. This study aimed to assess resistance of clinical isolates from Libyan hospitals to antipseudomonal antibiotics, the prevalence of selected extended-spectrum β-lactamases and carbapenemase genes among these isolates, and the microorganisms’ capacity for alginate and biofilm production. Forty-five isolates were collected from four hospitals in Benghazi and Derna, Libya. Antimicrobial susceptibility was determined using agar disc diffusion. The presence of resistance genes (blaCTXM, blaTEM, blaSHV-1, blaGES-1, blaKPC, and blaNDM) was screened using PCR. Biofilm formation was quantified via the crystal violet assay, while alginate production was measured spectrophotometrically. Resistance to antipseudomonal antibiotics ranged from 48.9% to 75.6%. The most prevalent resistance gene was blaNDM (26.7%), followed by blaGES-1 (17.8%). Moreover, all isolates demonstrated varying degrees of biofilm-forming ability and alginate production. No statistically significant correlation was found between biofilm formation and alginate production. The dissemination of resistant genes in P. aeruginosa, particularly carbapenemases, is of great concern. This issue is compounded by the bacteria’s biofilm-forming capability. Urgent intervention and continuous surveillance are imperative to prevent further deterioration and the catastrophic spread of resistance among these formidable bacteria.